Discovering the Influence of Microorganisms on Wine Color - Tofalo, Rosanna; Suzzi, Giovanna; Perpetuini, Giorgia (Frontiers in Microbiology, 2021)
Flavour, composition and quality of wine are influenced by microorganisms present on the grapevine surface which are transferred to the must during vinification. The microbiota is highly variable with a prevalence of non-Saccharomyces yeasts, whereas Saccharomyces cerevisiae is present at low number. For wine production an essential step is the fermentation carried out by different starter cultures of S. cerevisiae alone or in mixed fermentation with non-Saccharomyces species that produce wines with significant differences in chemical composition. During vinification wine color can be influenced by yeasts interacting with anthocyanin. Yeasts can influence wine phenolic composition in different manners: direct interactions – cell wall adsorption or enzyme activities – and/or indirectly – production of primary and secondary metabolites and fermentation products. Some of these characteristics are heritable trait in yeast and/or can be strain dependent. For this reason, the stability, aroma and color of wines depend on strain/strains used during must fermentation. Saccharomyces cerevisiae or non-Saccharomyces can produce metabolites reacting with anthocyanins and favor the formation of vitisin A and B type pyranoanthocyanins, contributing to a great color stability. In addition, yeasts affect the intensity and tonality of wine color by the action of β-glycosidase on anthocyanins or anthocyanidase enzymes or by the pigments adsorption on the yeast cell wall. These activities are strain dependent and are characterized by a great inter-species variability. Therefore, they should be considered a target for yeast strain selection and considered during the development of tailored mixed fermentations to improve wine production. In addition, some lactic acid bacteria seem to influence the color of red wines affecting anthocyanins’ profile. In fact, the increase of the pH or the ability to degrade pyruvic acid and acetaldehyde, as well as anthocyanin adsorption by bacterial cells are responsible for color loss during malolactic fermentation. Lactic acid bacteria show different adsorption capacity probably because of the variable composition of the cell walls. The aim of this review is to offer a critical overview of the roles played by wine microorganisms in the definition of intensity and tonality of wines’ color.